(untitled) (Albayan Scientific Journal, 2023)
The paper deals with the role of identity in the national struggle of Amilcar Cabral ‎(1924-1973), that he is a prominent political thinker who contributed to his distinctive revolutionary and philosophical ideas in building an anti-colonial and imperialist ideology, as well as drawing a new, expanded intellectual course of thought for Marx and Lenin’s philosophy to suit African reality. Cabral presented his idea of ​​the identity that he has in the problem of (the ego and the other) where the (ego) represents